Potret Kehidupan Sosial Ekonomi Nelayan Pantai Kuri Caddi Di Desa Nisombalia Kecamatan Marusu Kabupaten Maros - Hasmidar, Andi (LaGeografia, 2017)
This study was conducted to: socioeconomic characteristics of fishermen based (age, education level, income and number of dependents of fishermen). The research area was determined deliberately on the beach Kuri Caddi and sample withdrawal method used was simple rangdom sampling based on the society whose active as the fisherman with 30 people of the population, technique used is descriptive technical analysis.